Saleem Badat, The Forgotten People: Political Banishment under Apartheid: An overlooked, repressive tactic of apartheid revealed (Historia, 2021)
African and more specifically South African history is riddled with a heinous past; there are many struggle stories and notable figures that have been pushed into the shadows of silence. Lending voice to these injustices ensures a sense of reconciliation with the past and present, allowing future generations to move forward. Saleem Badat's The Forgotten People: Political Banishment under Apartheid, does just that by contributing to the historiography of repressive methods employed during the apartheid era, adding the neglected dimension of banishment as a repressive tactic to the list of atrocities. His book not only focuses on a largely overlooked form of repression, but also brings to light those who until now have been missing from our recorded history, by affixing "peasants and migrants as actors and shapers alongside the black proletariat [and] the heroes of the African nationalist struggle".